2018
DOI: 10.1002/celc.201800455
|View full text |Cite
|
Sign up to set email alerts
|

Recycling Antibiotic Bacterial Residues for Application in High‐Performance Lithium−Sulfur Batteries

Abstract: Antibiotic bacterial residue is a type of hazardous waste generated during the extraction of antibiotic. Owing to the large amount, difficult disposal, and negative impacts on the environment and human health of antibiotic bacterial residues, it is of great significance to find an efficient treatment and resource technology. In an effort to recycle antibiotic bacterial residues from “trash to treasure” and to target a high‐value application, antibiotic bacterial residues are utilized for the fabrication of nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 34 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…In the food industry, the production of fruit generated 266 million metric tons of pomace waste annually, which could be utilized for extracting 270 000 t of DNA . In the biopharmaceutical industry, the generation of microbial residues during antibiotic production was 14 million metric tons annually, providing 140 000 t of DNA every year . In the bioethanol industry, the data showed that the commercial market could provide 2 million metric tons of dry yeast annually to extract 6000 t of DNA .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the food industry, the production of fruit generated 266 million metric tons of pomace waste annually, which could be utilized for extracting 270 000 t of DNA . In the biopharmaceutical industry, the generation of microbial residues during antibiotic production was 14 million metric tons annually, providing 140 000 t of DNA every year . In the bioethanol industry, the data showed that the commercial market could provide 2 million metric tons of dry yeast annually to extract 6000 t of DNA .…”
Section: Discussionmentioning
confidence: 99%
“…67 In the biopharmaceutical industry, the generation of microbial residues during antibiotic production was 14 million metric tons annually, providing 140 000 t of DNA every year. 68 In the bioethanol industry, the data showed that the commercial market could provide 2 million metric tons of dry yeast annually to extract 6000 t of DNA. 54 In the bloomed algae industry, the commercial production of dry algae was 15 000 t annually, enabling the extraction of 450 t of DNA every year.…”
Section: ■ Discussionmentioning
confidence: 99%